Antioxidant enzymes in periodontitis - Shilpa Trivedi; Nand Lal (Journal of Oral Biology and Craniofacial Research)
Periodontitis is basically an inflammatory disease initiated by the subgingival biofilm and modified by the individual's aberrant inflammatory/immune response. Various studies have pointed toward the role of oxidative stress in periodontitis. As the reactive oxygen species and antioxidants are in dynamic equilibrium, any disturbance in one would lead to changes in the other. As studying, individual antioxidants is a vast field, this review focuses on the role of antioxidant enzymes in periodontitis and in other related systemic conditions. It is highlighted that oxidative stress may be the missing link in these associations of periodontitis and other conditions. Also, the antioxidant enzymes may be considered a useful biomarker for periodontal diseases and antioxidant supplementation may be of help to reduce the burden of periodontal destruction without having much extra effort.